PERBEDAAN TRANSMISI TEKANAN PADA BASIS GIGI TIRUAN RESIN AKRILIK POLIMERISASI PANAS DAN NILON TERMOPLASTIK - Crystal, Elis; Nasution, Hubban (Jurnal Ilmiah PANNMED (Pharmacist, Analyst, Nurse, Nutrition, Midwivery, Environment, Dentist), 2019)
The purpose of this study was to evaluate The Difference in Pressure Transmission between Polymethyl-Methacrylate (PMMA) and Thermoplastic Nylon Denture Based. Material and methods: Mandibular first molar acrylic denture teeth (Bioeco) embedded on 15x15x3 mm3 thermoplastic nylon (Biotone) and poly methyl methacrylate denture bases were evaluated (n=9). A 100N force applied on the specimen using universal testing machine and the pressure transmitted under the specimen observed using pressure transducer. Results: The results showed that polymethyl methacrylate has the highest pressure transmission compared to thermoplastic nylon. This study can help dentists to determine the design of dentures, especially in the selection of denture base materials.